Kesejahteraan Ibu dan Anak: Implementasi ASI Eksklusif bagi Wanita Karir Berdasarkan Pasal 11 Ayat (1) UU No. 4 Tahun 2024 dan Perspektif Maqashid Syari'ah - Any Sani’atin, St. Ika Noerwulan Fraja, Ainur Gufron, Arif Rahman, Mohammad Ramdan, Syamsul Rizal, I (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2025)
The provision of exclusive breastfeeding for the first six months is a child’s right as well as a mother’s obligation, as regulated in various national laws, including Article 11 paragraph (1) of Law No. 4 of 2024 on Maternal and Child Welfare. However, its implementation often faces challenges, particularly for career women who must balance professional responsibilities with their breastfeeding duties. This study aims to analyze the implementation of exclusive breastfeeding policies for career women and to examine their relevance from the perspective of Maqashid Shari‘ah, especially in the aspects of hifz al-nafs (protection of life) and hifz al-nasl (protection of progeny). The research employs a normative juridical method with a qualitative approach, supported by secondary data in the form of statutory regulations, Islamic literature, and implementative case studies. The findings indicate that although the regulations provide a strong legal foundation, practical implementation still encounters obstacles such as the lack of lactation facilities in workplaces, limited awareness among employers, and weak supervision. From the perspective of Maqashid Shari‘ah, fulfilling the right to exclusive breastfeeding constitutes part of protecting future generations and the fundamental rights of children, in line with Islamic principles. Therefore, synergy between regulations, social awareness, and institutional commitment is essential to ensure the holistic welfare of mothers and children